Pharmacological PI3K inhibition in head and neck squamous cell carcinoma: A systematic review. (April 2023) - Alves, L.B.; Moura, A.C.; Amorim dos Santos, J.; Borges, G.A.; Guerra, E.N.S.
Abstract: Background: This systematic review aimed to investigate the in vitro and in vivo effects of phosphatidylinositol-3-kinase (PI3K) inhibitors on head and neck squamous cell carcinoma (HNSCC). Considering the role of PI3K and its downstream effectors in cell proliferation, invasion, and survival, it is reasonable to expect that treatment with PI3K inhibitors could control HNSCC onset and progression. Thus, the research question for our review was whether pharmacological inhibition of PI3K affects HNSCC progression. Methods: In vitro and in vivo studies were selected from six databases. We collected data regarding cell viability, apoptosis, and the regulation of protein expression levels from in vitro studies. For the in vivo studies, we analyzed the reduction in tumor size or gene and protein expression. Results: The included studies showed reduced cell proliferation and apoptosis after treatment with PI3K inhibitors. PI3K inhibitors in combination with other drugs had an enhanced anticancer effects compared to those of single-drug treatments. Conclusions: The results support the potential of PI3K inhibitors as candidates for clinical trials in HNSCC. Highlights: PI3K-AKT-mTOR pathway mutations rank as the second most significant in human cancers. This is the first review that summarizes the importance of PI3K inhibitors. This study provides a platform for researchers to summarize the antitumor effects of PI3K inhibitors in HNSCC. HPV (+) cells were more resistant to inhibitors than HPV (−).